Transcriptome analysis of poplar rust telia reveals overwintering adaptation and tightly coordinated karyogamy and meiosis processes - HACQUARD, Stéphane; Delaruelle, Christine; Frey, Pascal; Tisserant, Emilie; Kohler, Annegret; Duplessis, Sébastien (Frontiers in Plant Science, 2013)
Most rust fungi have a complex life cycle involving up to five different spore-producing stages. The telial stage that produces melanised overwintering teliospores is one of these and plays a fundamental role for generating genetic diversity as karyogamy and meiosis occur at that stage. Despite the importance of telia for the rust life cycle, almost nothing is known about the fungal genetic programs that are activated in this overwintering structure. In the present study, the transcriptome of telia produced by the poplar rust fungus M. larici-populina has been investigated using whole genome exon oligoarrays and RT-qPCR. Comparative expression profiling at the telial and uredinial stages identifies genes specifically expressed or up-regulated in telia including osmotins/thaumatin-like proteins and aquaporins that may reflect specific adaptation to overwintering as well numerous lytic enzymes acting on plant cell wall, reflecting extensive cell wall remodelling at that stage. The temporal dynamics of karyogamy was followed using combined RT-qPCR and DAPI-staining approaches. This reveals that fusion of nuclei and induction of karyogamy-related genes occur simultaneously between the 25-39 days post inoculation time frame. Transcript profiling of conserved meiosis genes indicate a preferential induction right after karyogamy and corroborate that meiosis begins prior to overwintering and is interrupted in Meiosis I (prophase I, diplonema stage) until teliospore germination in early spring.